2007
DOI: 10.1007/s12011-007-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Erdosteine and Vitamins C and E Combination on Ischemia–Reperfusion-Induced Lung Oxidative Stress and Plasma Copper and Zinc Levels in a Rat Hind Limb Model

Abstract: The aim of this study was to investigate the protective effects of erdosteine and vitamins C and E (VCE) on the lungs after performing hind limb ischemia-reperfusion (I/R) by assessing oxidative stress, plasma copper (Cu), and zinc (Zn) analysis. The animals were divided randomly into four groups as nine rats each as follows: control, I/R, I/R plus erdosteine, and I/R plus VCE combination. I/R period for 60 min was performed on the both hind limbs of all the rats in the groups of I/R, erdosteine with I/R, VCE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…4,5 The role of neutrophils and oxidative damage in the lung and liver following lower I/R injury is well documented. 17,18,22 Increased alveolar fluid gene expression for tumor necrosis factor-a, interferon-g, interleukin-1b, and macrophage inflammatory protein-2 have been found in anesthetized rats after inhalation of volatile anesthetics. 23 However, the authors did not study anesthesia conducted with desflurane.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The role of neutrophils and oxidative damage in the lung and liver following lower I/R injury is well documented. 17,18,22 Increased alveolar fluid gene expression for tumor necrosis factor-a, interferon-g, interleukin-1b, and macrophage inflammatory protein-2 have been found in anesthetized rats after inhalation of volatile anesthetics. 23 However, the authors did not study anesthesia conducted with desflurane.…”
Section: Discussionmentioning
confidence: 99%
“…The biomedical roles of Se include its actions in the antioxidant defense against oxidative stress, protection against cardiovascular diseases, cancers, and physiological functions in the nervous system [8][9][10]. It has been shown that selenium exerts protective effects against ischemia-reperfusion of lung [11], brain disorders [12], and chemotherapeutic drug-induced liver oxidative injury [13]. These effects of selenium are attributed to its role in reducing oxidative stress and inhibition of apoptosis [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…25,35 In addition to its mucolytic action, Met I also is an useful antioxidant. 13 In current study, we showed histopathological changes such as cellular disruption, cell vacuolization and central necrosis in rats received RCM. These changes show that RCM administration lead to cellular disruption and hepatocellular necrosis in liver tissue.…”
Section: Discussionmentioning
confidence: 56%
“…9,13 Administration of RCM is characterized by activation of the inflammatory response system. 12,23 TBARS levels is a major oxidative degradation product of membrane unsaturated fatty acid and has been shown to be biologically active with ROS properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation